An Embattled Yet Enduring Influence: Introduction to a Special Issue on Blumerian Symbolic Interactionism. Issue 4 (1st October 2020) - Low, Jacqueline; Bowden, Gary
Abstract : The papers in this special issue celebrate and build on the insights Blumer provides in his pivotal book Symbolic Interactionism: Perspective and Method. In setting the context for these papers, we discuss the significance of Blumer's variant of interactionism, his contributions to the discipline of sociology, the misinterpretations and misrepresentations of his approach, and the way in which the papers in this issue carry forward his legacy.